Family-Centered Approach to Chronic Abdominal Pain in a Teacher : A Holistic Perspective - Setijowati, Nanik; Kuntadi, Muhammad; Zarithsyafiqah, Siti (Jurnal Ilmu Kedokteran Keluarga, 2025)
Chronic abdominal pain, a prevalent yet often multifactorial complaint in primary care, frequently extends beyond purely biomedical etiologies to encompass significant psychosocial stressors and family dynamics. This case report highlights the importance of a holistic, family-centered approach in diagnosing and managing such conditions, moving beyond a narrow symptomatic focus. We present the case of a 35-year-old female kindergarten teacher experiencing recurrent right lower abdominal bloating and pain for three days, exacerbated by activity and alleviated by rest. Associated symptoms included nausea, irregular bowel movements (once every three days), and feelings of overwhelm due to work and domestic responsibilities. Despite her concerns about a prior hepatomegaly during her second pregnancy, physical examination and initial assessment pointed towards a more generalized abdominal discomfort influenced by lifestyle and stress. This case illustrates how chronic abdominal discomfort, initially perceived by the patient as a singular biomedical issue, can be intricately linked to a confluence of biological, psychological, and social factors. The patient's irregular eating habits, high coffee consumption, lack of exercise, and significant work-life imbalance contributed to her symptoms. While an initial diagnosis of acute gastritis was considered, the persistent nature and association with stress suggest a broader functional gastrointestinal disorder. The family APGAR score of 9 indicated a highly functional family unit, yet the Family SCREEM identified cultural factors (husband's limited domestic involvement) and the patient's poor stress management as potential contributors. Comprehensive intervention involved patient education on lifestyle modification, stress management techniques, and family involvement to alleviate domestic burdens. This case underscores the necessity of a comprehensive, family-oriented approach in managing chronic abdominal pain. By addressing not only the physical symptoms but also the underlying psychosocial stressors and family dynamics, healthcare providers can facilitate more effective and sustainable patient outcomes. This holistic perspective aligns with the principles of family medicine, advocating for interventions that consider the patient within their unique family and community context.